Inheritance of white colour in Alpacas: Identifying the genes involved - Munyard, Kylie (Rural Industries Research and Development Corporation, 2013)
This RIRDC report describes the research conducted as part of the alpaca colour genetics project to identify the genes involved in the inheritance of white colour in alpacas. Three approaches were used (Mendelian, physical and genetic) in an attempt to unravel the mystery surrounding colour inheritance in alpacas. This project has successfully identified key mutations in genes that lead to differences in fibre colour in alpacas. Other genes, which play a role in colour variation in other species, were cleared of involvement in colour variation in alpacas. Through extensive observational analysis a model for Mendelian inheritance of the major colours was developed. In combination, these findings provide breeders with information that allows them to make informed colour breeding choices.